2007
DOI: 10.1016/j.bone.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired posterior frontal sutural fusion in the biglycan/decorin double deficient mice

Abstract: Biglycan (Bgn) and decorin (Dcn) are highly expressed in numerous tissues in the craniofacial complex. However, their expression and function in the cranial sutures is unknown. In order to study this, we first examined the expression of biglycan and decorin in the posterior frontal suture (PFS), which predictably fuses between 21-45 days post-natal and in the non-fusing sagittal (S) suture from wildtype (Wt) mice. Our data showed that Bgn and Dcn were expressed in both cranial sutures. We then characterized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
1
32
0
2
Order By: Relevance
“…Decorin and biglycan are considered to regulate calvarial bone formation in developmental processes by interacting with BMPs from the study of knockout mice (Wadhwa et al, 2007). The present study showed that the differentiation of MC3T3-E1 cells, established from murine calvaria, is controlled by CS or DS chains of PGs in vitro, supporting the in vivo phenotype alteration.…”
Section: Journal Of Cellular Physiology C H O N D R O I T I N S U L Fmentioning
confidence: 50%
“…Decorin and biglycan are considered to regulate calvarial bone formation in developmental processes by interacting with BMPs from the study of knockout mice (Wadhwa et al, 2007). The present study showed that the differentiation of MC3T3-E1 cells, established from murine calvaria, is controlled by CS or DS chains of PGs in vitro, supporting the in vivo phenotype alteration.…”
Section: Journal Of Cellular Physiology C H O N D R O I T I N S U L Fmentioning
confidence: 50%
“…In addition to the tendon, several studies suggest functional compensation for decorin by biglycan in single null models. For example, the posterior frontal suture of the developing calvaria fuses normally in the absence of either decorin or biglycan, but fails to fuse in mice null for both SLRPs [25]. Mice that lack both decorin and biglycan exhibit a collagen fibril morphology that is significantly more abnormal than either single deficiency, which supports the hypothesis that they have overlapping functions that permit functional compensation in single null mice [8, 23].…”
Section: Introductionmentioning
confidence: 85%
“…Decorin is thought to regulate Transforming growth factor beta (TGFB) bioavailability and mutations in this gene have been linked to Marfan syndrome [37], [38]. Decorin has also been identified at the cranial suture with importance for suture formation and growth linked to its expression [39]. In addition, a study investigating the effects of FGF2 administration to Crouzon Syndrome (FGFr Autosomal Dominant Craniosynostosis Syndrome) patient derived parietal bone osteoblasts suggested an inverse relationship between FGF2 and DCN [40].…”
Section: Discussionmentioning
confidence: 99%